Integrating the results of user research into medical device development: insights from a case study - Martin, Jennifer L.; Barnett, Julie (Biomed Central, 2012)
Background: It is well established that considering users is an important aspect of medical device development. However it is also well established that there are numerous barriers to successfully conducting user research and integrating the results into product development. It is not sufficient to simply conduct user research, it must also be effectively integrated into product development. Methods: A case study of the development of a new medical imaging device was conducted to examine in detail how users were involved in a medical device development project. Two user research studies were conducted: a requirements elicitation interview study and an early prototype evaluation using contextual inquiry. A descriptive in situ approach was taken to investigate how these studies contributed to the product development process and how the results of this work influenced the development of the technology. Data was collected qualitatively through interviews with the development team, participant observation at development meetings and document analysis. The focus was on investigating the barriers that exist to prevent user data from being integrated into product development. Results: A number of individual, organisational and system barriers were identified that functioned to prevent the results of the user research being fully integrated into development. The user and technological aspects of development were seen as separate work streams during development. The expectations of the developers were that user research would collect requirements for the appearance of the device, rather than challenge its fundamental concept. The manner that the user data was communicated to the development team was not effective in conveying the significance or breadth of the findings. Conclusion: There are a range of informal and formal organisational processes that can affect the uptake of user data during medical device development. Adopting formal decision making processes may assist manufacturers to take a more integrated and reflective approach to development, which should result in improved business decisions and a higher quality end product.